2019
DOI: 10.1038/s41385-019-0198-5
|View full text |Cite
|
Sign up to set email alerts
|

Small heat shock protein CRYAB inhibits intestinal mucosal inflammatory responses and protects barrier integrity through suppressing IKKβ activity

Abstract: Alpha B-crystallin (CRYAB) is an important member of the small heat shock protein family, and plays a protective and therapeutic role in neurological inflammation. CRYAB expression was assessed in cultured HT29 and Caco-2 cells and inflamed mucosa of patients with inflammatory bowel disease (IBD) and colitis models in mice. Lentivirus-overexpressing and CRSIPR/Cas9 systems were used in different cells to upregulate and silence CRYAB expression, respectively. Cell permeable recombined fusion protein TAT-CRYAB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…It is worth noting that activation of canonical NF-κB pathway mediated by IKKβ showed relevance to CRYAB blockade, while NIK/IKKα remained invariant. What we testified was consistent with previous studies, in which CRYAB was proved to be a potent negative regulator of noncanonical NF-κB signal 14 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is worth noting that activation of canonical NF-κB pathway mediated by IKKβ showed relevance to CRYAB blockade, while NIK/IKKα remained invariant. What we testified was consistent with previous studies, in which CRYAB was proved to be a potent negative regulator of noncanonical NF-κB signal 14 .…”
Section: Discussionsupporting
confidence: 90%
“…As an important member of small heat-shock protein, CRYAB displays a proper role with identification of the anti-inflammatory effect 12,13 . Recent studies indicated that CRYAB could serve as a potential target in response to stimulation of inflammatory cytokines, through suppression of IKK in intestinal mucosal inflammation 14 . Given the pivotal role of IKK in the initiation of NF-κB signaling, CRYAB is likely to control the occurrence and progress of inflammation in hepatic IRI to some extent, the specific molecular mechanism of which needs an indepth exploration 8,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Screening of molecules able to decrease CF chronic inflammation is an active area of research [37]. Recently, Xu et al [38] reported that HspB5 mRNA expression was decreased in inflamed mucosa of inflammatory bowel disease patients compared to noninflamed specimens. Interestingly, TAT-HspB5 recombinant protein administration alleviated intestinal mucosal inflammation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the administration of recombinant HSPB5 protein ameliorates EAE, suggesting an immunosuppressive and therapeutic role for HSPB5 during autoimmune demyelination [ 158 ]. Similarly, HSPB5 was found to regulate intestinal inflammation that inhibits IKKβ-mediated signaling to alleviate colitis symptoms and protect intestinal barrier integrity in animals [ 159 ]. The immune balance handled by sHSPs is dependent on their local concentrations.…”
Section: Roles Of Molecular Chaperones In Metabolism and Immune Fumentioning
confidence: 99%